A Kannappan-cosine functional equation on semigroups - Jafar, Ahmed; Ajebbar, Omar; Elqorachi, Elhoucien (Annales Mathematicae Silesianae, 2024)
In this paper we determine the complex-valued solutions of the Kannappan-cosine functional equation g(xyz0) = g(x)g(y) − f(x)f(y), x,y∈S, where S is a semigroup and z0 is a fixed element in S.